Application Of Titonia diversifolia As A Biopesticide In Soybean Cultivation In Meureubo District, West Aceh - Putri Mustika Sari; Chairudin Chairudin; Vina Maulidia; Rayhan Amadius Weihan (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2023)
The tsunami that occurred in 2004 has changed various aspects of activities in West Aceh District. Particularly in the agricultural aspect, the damage occurred not only to cultivated land but also to the surrounding ecosystem. Particularly in the Meureubo sub-district there is a need for outreach to improve farming, where cultivated plants are often attacked by pests. So it is necessary to have proper and environmentally friendly control, one of which is by increasing the use of biopesticides derived from wild plants that are easy to find. Titonia is a flowering wild plant that has the potential to be a good source of nutrition for organic plants, T. diversifolia can be used as green manure, and there are several other studies which also state that titonia extract can be used as a vegetable pesticide in pest control. Using the direct field observation method, which aims to provide knowledge to farmer groups in Meureubo District, West Aceh to use Titonia as an environmentally friendly biopesticide in agricultural cultivation, where the future impact can restore the ecosystem on agricultural land by reducing the use of chemical pesticides. With the results of case study activities, namely biopesticide products that can be used by farmers, data on insects found on agricultural land, both pests, parasitoids, predators, and pollinators. The pests found on the cultivated land were Epilachna sp, Naupactus leucoloma, Piezodorus guildinii, Bemicia tabaci, Agromyza phaseoli, Nezara viridula, Spodoptera sp. By finding few types of pests, it means that the use of biopesticides can reduce the types of pests that attack agricultural land.